2005
DOI: 10.1002/ejic.200500393
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition – Allosterism Generated by Weak Host–Guest Interactions in Molecular Rectangles

Abstract: Two metal‐based molecular rectangles that bear two identical binding sites form 1:2 host–guest adducts with a pair of analogous planar Pt2+ complexes. The larger of the two guests shows no binding allosterism with either of the two rectangles, but substantial positive allosterism is observed when the smaller guest binds to the rectangles. It is proposed that the smaller guest is better accommodated in the binding sites of the receptor and that this leads to allosterism. Various experiments, including 1H NOESY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 26 publications
1
55
0
Order By: Relevance
“…The dinuclear Pt(II) cleft 161 was able to selfassemble into molecular rectangles 186 and 188 at high reaction temperatures. 163 The single crystal X-ray structure of tetranuclear 186 is depicted in Figure 70 (hydrogens, counterions, and part of the bis-terpyridine ligand were omitted for clarity).…”
Section: Dyads and Triadsmentioning
confidence: 99%
“…The dinuclear Pt(II) cleft 161 was able to selfassemble into molecular rectangles 186 and 188 at high reaction temperatures. 163 The single crystal X-ray structure of tetranuclear 186 is depicted in Figure 70 (hydrogens, counterions, and part of the bis-terpyridine ligand were omitted for clarity).…”
Section: Dyads and Triadsmentioning
confidence: 99%
“…This is a rare example of the strong allosteric effect directed by metal-metal interactions. [17] In summary, we demonstrated that the unique doubledecker tweezers-type host complexes 1 and 2, based on phosphorescent alkynyl platinum(II) polypyridine systems, could show significant host-guest interactions with interesting spectroscopic changes. The host-guest mixtures include various assemblies of positively, neutral, and negatively charged platinum(II) complexes organized in an unprecedented well-defined and controlled manner, which is in contrast to previous studies where difficulties for the fine control of assembly were reported.…”
Section: Methodsmentioning
confidence: 75%
“…[15] In the 1980's, Thummel and Jahng presented the synthesis of annelated 2,2Ј:6Ј,2"-terpyridines 4, [16] and Zimmerman et al developed a route to such terpyridines with additional functionalities in the α-position relative to the outer nitrogen atoms, eventually leading to the construction of partially shielded systems such as molecular pincers, [17] which were also found to act as host systems for organic guests and transition-metal ions. [18] At present, the most effective way of synthesizing bimacrocyclic concave reagents such as concave 1,10-phen- [ General structure for a concave 1,10-phenanthroline 5. [11][12][13][14] X and Y may be polymethylene or oligoethylene glycol chains.…”
Section: Introductionmentioning
confidence: 99%